Mitochondrial Copies Number and Some Renal Function Biomarkers in Type 2 Diabetes Mellitus on Metformin - Sameer Yonus, Samara; Ahmed AlKataan, Muhammad Abdulgafoor (Iraqi Journal of Pharmaceutical Sciences, 2022)
One of the most common metabolic illnesses in the world is diabetes mellitus. This metabolic disease is responsible for a large percentage of the burden of kidney damage and dysfunction. The goal of this study was to look into the renal function of diabetic patients using metformin monotherapy who came to Mosul’s Al-Wafaa diabetes care and research facility. During the period 1 January 2021 to 30 April 2021, 47 patients with T2DM (age 50.48 7.74 years) were enrolled in this case-control study. These patients’ results were compared to a control group of 47 seemingly healthy people (age 45.89 9.06 years). All participants’ demographic and medical histories were acquired through the delivery of a questionnaire. Blood samples were collected and tested for the mt-ND1 gene, HbA1c, uric acid, urea, and creatinine, among other things. In diabetics, there were extremely significant increases in HbA1c, Urea, and Creatinine (p < 0.001, 0.003, and 0.043, respectively) when compared to the control group. In diabetic patients, however, uric acid levels did not change significantly. HbA1c and uric acid had a strong negative connection (r = -0.045 and 0.05, respectively). In diabetic individuals, the number of mitochondrial copies was substantially lower than in the control group (p < 0.001). In comparison to non-diabetic controls, diabetic patients treated with mono-metformin treatment had a lower mitochondrial copy number and moderate renal impairment.